Make Their Dreams Come True! - Dow Chemical Company (1952)
Color print advertisement for Styron 475, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications. The advertisement features sets of small plastic toys against a blue-and-white background, with small figures of sleeping children. The accompanying text describes the use of Styron 475, "the new Dow plastics that is famous for its strength," in plastic toys and other consumer goods.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Plastic toys; Children in advertising